Karihwaientáhkwen: Conceptualizing Morality in Indigenous Consciousness - Deer, Frank; Heringer, Rebeca (Journal of Contemporary Issues in Education, 2024)
Many public institutions, including universities and colleges, have committed to Indigenous engagement – the institutional effort to engage with experiences, histories, and perspectives of First Nations, Inuit, and Métis peoples in meaningful ways. In many areas of institutional endeavour, these commitments have frequently included a focus upon spiritual orientations of Indigenous peoples as a central aspect of their knowledge and worldviews. In this study, we sought to acquire knowledge on moral understandings that were resident in the consciousness of Indigenous Elders and Knowledge Keepers situated at universities across Canada. Findings revealed that personal and communal experiences informed a developed sense of responsibility that may be situated in the unique manifestations of their respective knowledge systems, heritages, and consciousnesses. Although non-Indigenous orientations such as those of Christianity informed the narratives of some, a prevailing sense of traditional identity emerged from participants.